Assessing proprioception: A critical review of methods - Jia Han; Gordon Waddington; Roger Adams; Judith Anson; Yu Liu (Journal of Sport and Health Science, 2016)
To control movement, the brain has to integrate proprioceptive information from a variety of mechanoreceptors. The role of proprioception in daily activities, exercise, and sports has been extensively investigated, using different techniques, yet the proprioceptive mechanisms underlying human movement control are still unclear. In the current work we have reviewed understanding of proprioception and the three testing methods: threshold to detection of passive motion, joint position reproduction, and active movement extent discrimination, all of which have been used for assessing proprioception. The origin of the methods, the different testing apparatus, and the procedures and protocols used in each approach are compared and discussed. Recommendations are made for choosing an appropriate technique when assessing proprioceptive mechanisms in different contexts.